Interpolation rational integral fraction of the Hermitian-type on a continual set of nodes - Ya. O. Baranetskij; I. I. Demkiv; M. I. Kopach; A. V. Solomko (Математичні Студії, 2021)
Some approaches to the construction of interpolation rational integral approximations with arbitrary multiplicity of nodes are analyzed. An integral rational Hermitian-type interpolant of the third order on a continual set of nodes, which is the ratio of a functional polynomial of the first degree to a functional polynomial of the second degree, is constructed and investigated. The resulting interpolant is one that holds any rational functional of the resulting form.